Automated agriculture terms dictionary using string parsing / Nur Syahida Ahmad Zubaidillah - Ahmad Zubaidillah, Nur Syahida (2014)
This paper proposed the task of generating terms dictionary in the Agriculture domain. Its purpose is to generate only important terms using in Agriculture fields from Hypertext Mark-up Language (.html) file and Word Document (.doc) file as the input. The goal is to create a prototype which can automatically read the string from this type of file and then extracts their terms. The limitation of the previous manual work for generating terms are known to be labour-intensive, limitation of applicability and time consuming. Terms extracted are the smallest fragments of texts in documents, rather than the entire documents that contain the texts. After analyzing the characteristics of terms in Agriculture Dictionary, we propose a string parsing method to deal with the task.